A influência dos mecanismos internos da governança corporativa sobre as práticas de gerenciamento de resultados das instituições financeiras no Brasil - Bertoncelo, Valeria Regina (2020)
Earnings management associated with corporate governance mechanisms are relevant and recurring themes in the academic literature. The interest is given mainly because the use of discretion directly affects the profit for the year. Metric widely used for the fulfillment of contractual obligations (debt covenants), for the evaluation of the issue of tradable shares on the stock exchange, for the composition of the variable remuneration of the Board of Directors and their respective Committees, for the payment of dividends, etc. On the other hand, most corporate governance studies are based on developed markets, like United States of America and Europe. In emerging countries, such as Brazil, corporate governance structures can differ significantly, from aspects of capital structure, property and cultural issues and even to internal corporate governance mechanisms. The question that remains in this context is whether the discretionary use of earnings management can be minimized through the internal mechanisms of corporate governance, for different economic periods - expansion and recession, applied to financial institutions in Brazil. The results indicate evidence of earnings management and that the internal mechanisms of corporate governance have simultaneity biases